Effects of Ganoderma Lucidum Crude Polysaccharides on the Growth of Bifidobacteria and Other Selected Intestinal Bacteria - Hamdan Mustafa, Mohd Hamim (2009)
Ganoderma lucidum (G. lucidum) is a fungus commonly used as a traditional Chinese medicine. The high value of G. lucidum is related to its polysaccharides content. The polysaccharides are all glucan that are closely related to scleroglucan, but vary in their water solubility and in their degree and nature of their side chains. G. lucidum crude polysaccharides from (GLCP) were obtained by hot water extraction. There was about 0.56 g of GLCP in 1 g G. lucidum. Fractionation of GLCP lead to the isolation of four polysaccharides sub fractions, PF-1, PF-2, PF-3 and PF-4 with molecular weight of 2.3 x 104, 4.6 x 104, 1 x 105 and 3 x 105 Da respectively. The growth of probiotic bacteria (Bifidobacterium longum BB536, Bifidobacterium pseudocatenulatum G4, Lactobacillus acidophilus and Lactobacillus casei shirota) and other selected intestinal bacteria (Enterococcus faecalis JCM5803 and Salmonella choleraesuis JCM6977) were studied in 10 mL Trypticase Phytone Yeast (TPY) medium containing various concentrations of GLCP (0.5%, 1.0%, 1.5% and 2.0%) (TPYgl). The growth was compared to the growth in TPY medium supplemented with glucose and inulin. The growth in a basal TPY medium (TPYp), the medium with glucose (TPYglu) and a TPY medium containing both GLCP and glucose (TPYglu+gl) were also studied. Viable cell counts of the bacteria and the pH of the media were determined during anaerobic incubation of 0 h, 12 h, 24 h and 48 h at 37°C. In the absence of any carbohydrate source, all bacteria tested showed growth with mean log cfu/mL ranging from 6.87 to 7.99 after 24 hours incubation. However, in the presence of carbohydrate sources, cultures showed various degree of growth relative to the growth in TPYp. The bacteria tested showed highest growth in TPYglu+gl, followed by growth in TPYglu, TPYinu, TPYgl and TPYp sequentially. Highest viability of bacteria was observed in the media with the highest concentration of each carbohydrate source. Maximum population of bacteria was achieved after 24 hours and decreased significantly (p<0.05) after 48 hours in all media tested. B. longum BB536 showed the highest growth in TPYgl medium. At 24 hours incubation, highest population 10.53 log cfu/mL of B. longum BB536 was observed in medium with 2.0% GLCP and the lowest 9.37 log cfu/mL was in 0.5% concentration. B. pseudocatenulatum G4 was the second highest growth with 10.40 log cfu/mL. E. faecalis was the least growth (10.15 log cfu/mL) in this medium. Growth of B. pseudocatenulatum G4, E. faecalis JCM5803 and S. choleraesuis JCM6977 in GLCP fractions (TPYF1, TPYF2, TPYF3 and TPYF4) were compared to their growth in TPYinu 250 μg/mL (control). Results show that, all four fractions could support the growth of bacteria tested. The highest growth was the B. pseudocatenulatum G4 in TPYF2 with 1000 μg PF-2/mL concentrations. The growth was increased from 6.82 to 8.91 log cfu/mL after 24 hours and decreased to 7.92 log cfu/mL after 48 hours. In medium with 250 μg/mL PF-2, there was no significant (p<0.05) growth difference compared to control. This suggested that, all the four fractions and inulin are supporting the growth of this bacterium. E. faecalis JCM5803 and S. choleraesuis JCM6977 showed similar growth pattern. Comparing among the different media, these bacteria showed a very high growth in TPYF1. This was followed by growth in TPYF2, TPYF3 and TPYF4. High concentration of each fraction gave high viability of the bacteria. Highest population (8.89 and 8.72 log cfu/mL) was in the TPYF1 with 1000 μg/mL PF-1 after 24 hours incubation. This study shows that, GLCP could support the growth of bacteria tested. GLCP shows high potential of growth effect to bifidobacteria compared to other bacteria. Moreover, B. pseudocatenulatum G4 showed highest population in TPYF2 fraction compared to other bacteria tested. This suggested that PF2 of GLCP exhibited growth promoting effect on bifidobacteria. However, more study should be done to support this finding.